1923
DOI: 10.1021/ja01655a020
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF THE METHOD OF DESICCATION ON THE CARBOHYDRATES OF PLANT TISSUE1

Abstract: The iron division precipitate is treated directly with nitric acid and potassium chlorate to remove the manganese. (At this point phosphates may be removed if present.) Iron is removed by adding a large excess of ammonium hydroxide. The filtrate from the iron precipitate is evaporated until Only a faint odor of ammonia remains and nickel is tested for by adding dimethyl glyoxime directly to V6 of this solution, no adjustment of hydrogen ion being necessary.The remainder of the solution is further evaporated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1933
1933
1973
1973

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…The literature on heat-drying substantiates the early 1920 observations of Link and Tottingham (18) and Link (17) that no one method can be relied on for all plant parts and species. This also may be the case with the form of tissue used since it has been shown that method of drying does not equally affect fresh and ensiled herbage (7,27).…”
Section: Influence Of Tissue Drying Conditionssupporting
confidence: 54%
See 1 more Smart Citation
“…The literature on heat-drying substantiates the early 1920 observations of Link and Tottingham (18) and Link (17) that no one method can be relied on for all plant parts and species. This also may be the case with the form of tissue used since it has been shown that method of drying does not equally affect fresh and ensiled herbage (7,27).…”
Section: Influence Of Tissue Drying Conditionssupporting
confidence: 54%
“…Link and Tottingham (18) and Link (17) found few heat-drying treatments that were suitable for all kinds of tissues. Drying at 60°t o 80°C in forced-draft ovens was satisfactory for some tissues.…”
Section: Influence Of Tissue Drying Conditionsmentioning
confidence: 99%
“…However, slow low-temperature drying is not to be recommended in these cases. Not only will the associated dry matter losses alter the proportions of the remaining constituents, but these themselves may be changed during the drying process (16). While r.f.…”
Section: Design and Testing Of An Improved Laboratory Ovenmentioning
confidence: 99%
“…Thus LINK (16) has shown considerable changes in the free and reducing sugar content of plant material during drying. This means that an estimation of, say, reducing sugar content of similar plant material before and after drying cannot be taken as a measure of the loss of reducing sugars during drying.…”
Section: Nature Of Dry Matter Lossesmentioning
confidence: 99%
“…On the other hand, the discolouration of oven-dried material would suggest that these determinations should be made on fresh herbage or freeze-dried material (15,23).…”
Section: Discussionmentioning
confidence: 99%